In Memoriam: Medicine's Confrontation with Evil - Seidelman, William E. (The Hastings Center report, 1989)
The proposed public burial of anatomical specimens derived from victims of the Nazis provides an occasion for the medical community worldwide to confront this legacy and the profession's ongoing potential for evil.